Analisis Kesuksesan Aplikasi M-Paspor di Kota Batam dengan Menggunakan Model Delone dan Mclean - Suwarno Liang; Mangapul Siahaan; Jocelyn Jocelyn (Jurnal Sistem Informasi Bisnis, 2024)
M-Paspor is a new version of the APAPO application launched at the end of 2021. Since the launch of the M-Paspor application, Indonesian citizens have been directed to submit passport queue applications through the M-Paspor. Batam City is a city that is on international shipping routes and borders directly with Singapore and Malaysia. With these advantages, many Indonesian citizens travel through the City of Batam, causing passport applications in the City of Batam to increase. This research aims to analyze the success of the M-Passport application in the City of Batam using the DeLone and McLean model. The method used in this research is a mixed method of qualitative and quantitative, with 30 qualitative data and 500 quantitative data collected. This research utilizes SPSS and AMOS technology to test validity, reliability, SEM, descriptive statistics, and R Square. The results obtained from this research show that all dependent variables have a positive effect on the independent variables with R Square values obtained as much as 61.3%, 58.9%, and 61.9%. By conducting this research, it is hoped that it can help M-Paspor application developers and the TPI Batam Class I Immigration Office to pay more attention to the quality of information, systems, and services from M-Paspor to improve increase public user satisfaction in public services.